A Multimodal Learning System for Individuals with Sensorial, Neuropsychological, and Relational Impairments. (14th July 2013) - Canazza, Sergio; Foresti, Gian Luca
Abstract : This paper presents a system for an interactive multimodal environment able (i) to train the listening comprehension in various populations of pupils, both Italian and immigrants, having different disabilities and (ii) to assess speech production and discrimination. The proposed system is the result of a research project focused on pupils with sensorial, neuropsychological, and relational impairments. The project involves innovative technological systems that the users (speech terabits psychologists and preprimary and primary schools teachers) could adopt for training and assessment of language and speech. Because the system is used in a real scenario (the Italian schools are often affected by poor funding for education and teachers without informatics skills), the guidelines adopted are low-cost technology; usability; customizable system; robustness.